Enhancing ultrasound-guided brachial plexus nerve localization with ResNet50 and support vector machine - Mummaneni, Sobhana; Kumar Chintakayala, Kushal; Mukund Yarlagadda, Lalith Sai; Naga Raju Ala, Venkata Siva; Vemulapalli, Nihitha (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Medical image segmentation and classification plays a vital role in nerve block/region identification, particularly for anesthesiologists relying on instinctual judgments. However, due to patient-specific anatomical variations, these methods sometimes lack precision. This research focuses on addressing the problem, by incorporating novel ensembling method of ResNet-50 and support vector machine (SVM) to achieve segmentation of dataset images and classification of nerve blocks respectively. The said novel ensemble model is trained on a publicly available dataset consisting of more than 16,800 images. The sole purpose of this work is to address the problem of peripheral nerve blocking (PNB) with the usage of ensemble modelling, while achieving the highest possible accuracy. This research will help practitioners in accurately identifying the location of brachial plexus and distinguishing the type of nerve block to be injected – interscalene and supraclavicular. The model, which integrates ResNet50 and SVM classifier, achieved a commendable 99.27% accuracy in identifying and classifying the brachial plexus region.